KOMUNIKASI PARTISIPATIF WARGA PADA BENGKULU REGIONAL DEVELOPMENT PROJECT (KASUS DI DESA PONDOK KUBANG KECAMATAN PONDOK KELAPA KABUPATEN BENGKULU TENGAH) - Mulyasari, Gita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
The successful of Bengkulu Regional Deoelopmeni Project was very determined by the society participation in all of the project activities. Without their participation, those activities would not be done as the expectation. In order to optimize the society's participation in the development project (BRDP), a good participative communication was needed to create a feedback between the people involved in BRDP and the society. This research is aimed to analyze: a) participating on communication in BRDP process, b) the factors influenced the participation between the society and facilitator in BRDP activities. The community participatory communication in the planning stage had a real connection with ability. The community participatory communication in the stage of process was very connected with the capability changer too. The members of UPKD had given chances to ask questions, opinions, and suggestions connected with BRDP activities in Pondok Kubang village, but the low of education, experience, and financial capital of the society resulted in their low participation in BRD P activities. The low capability also reduced their motivation to participate. The community participatory communication in the stage of evaluation had a real relation with the honesty changer. In this stage, the community expected the honesty UPKD and transparency in case